The Scope of the Truth and Reconciliation Commission in Canadian Francophone Contexts - Wiscutie-Crépeau, Nancy; Ng-a-Fook, Nicholas; Joncas, Jo Anni; Pageau, Laurie (Journal of the Canadian Association for Curriculum Studies, 2023)
This special issue examines the scope of the Truth and Reconciliation Commission (TRC) of Canada’s Calls to Action in Francophone educational contexts. This contribution presents emerging research conducted in Quebec and Ontario, and theoretical reflections proposed by researchers in the contexts of Quebec, Alberta and Saskatchewan. It examines the possibilities and limits of TRC calls to action in Francophone contexts, including the educational issues of indigenization, reconciliation, decolonization, identities, as well as educational policy and curriculum issues, in order to better understand the particular position of Francophone communities in the project of settlement colonialism in this country.